PERFORMANCE ASSESSMENT ANALYSIS OF SHARIA BANK USING THE SHARIA MAQASHID INDEX METHOD IN ACEH SHARIA BANK MEDAN - Andayani, Ambar Ikhsan; Hani, Syafrida (International Proceeding of Law and Economic, 2022)
This study aims to determine the condition of the performance of Bank Aceh Syariah which uses the sharia system seen from the maqashid sharia aspect using the maqashid sharia index method approach. This study uses three performance indicators, namely tahzib al-fard, iqamah al-adl, and jalb al-mashlahah. The research method used is quantitative research which is the object of research, namely Bank Aceh Syariah. The data used in this study is secondary data from the 2016-2018 Bank Aceh Syariah annual report. The performance ratio used is the ten maqashid sharia performance ratio index. Based on the calculation results show the performance of maqashid sharia can be done with the maqashid sharia index approach. Research shows the overall performance of the maqashid sharia index in 2016 to 2018 has increased and decreased. The average increase in the performance of the maqashid sharia index occurred in 2017 compared to 2016 and 2018.